2016
DOI: 10.1007/s10096-016-2851-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic hepatitis C infection on cholesterol metabolism in PBMCs is associated with microRNA-146a expression

Abstract: Chronic hepatitis C (CHC) infection is known to induce important changes in host cholesterol metabolism. MicroRNAs (miRNAs) regulate the expression of many genes and, in consequence, control various processes, including human metabolism and response to viral infection. Recently, the alteration of the immune-associated miR-146a, which is abundantly present in peripheral blood mononuclear cells (PBMCs), was found in some viral infections. The study aimed to analyse the influence of hepatitis C virus (HCV) infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Similar to miR-155, miR-146a is abundant in peripheral blood mononuclear cells and regulates the inflammatory and immune responses [ 28 ]. It has recently been reported that miR-146 was upregulated in HCV-infected cells, human primary hepatocytes and liver tissue of chronic hepatitis C infection patients [ 28 ].…”
Section: Mirnas Regulate the Immune Response To Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to miR-155, miR-146a is abundant in peripheral blood mononuclear cells and regulates the inflammatory and immune responses [ 28 ]. It has recently been reported that miR-146 was upregulated in HCV-infected cells, human primary hepatocytes and liver tissue of chronic hepatitis C infection patients [ 28 ].…”
Section: Mirnas Regulate the Immune Response To Hcvmentioning
confidence: 99%
“…Similar to miR-155, miR-146a is abundant in peripheral blood mononuclear cells and regulates the inflammatory and immune responses [ 28 ]. It has recently been reported that miR-146 was upregulated in HCV-infected cells, human primary hepatocytes and liver tissue of chronic hepatitis C infection patients [ 28 ]. On the other hand, decreased miR-146a expression has also been observed in peripheral blood mononuclear cells from patients with chronic hepatitis C. This can partially be explained as the studies analysed patients infected with different genotype HCV.…”
Section: Mirnas Regulate the Immune Response To Hcvmentioning
confidence: 99%
“… 35 HCV infection was also shown to boost the expression of miR-146, leading to an alteration of IFN concentrations in sera following HCV infection. 36 Similarly, other miRNAs, such as miR-130 and miR-21, have been described as participating in inflammatory and immune responses to HCV infection. 37 , 38 Based on the present findings in this study, we further accessed if miR-373 and IRF5 contribute to activation of type 1 IFN.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the methods of Sidorkiewicz et al 2017 [ 12 ]. Serum total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), and triglycerides (TG) were measured enzymatically in Olympus AU 640 and the kits of Olympus.…”
Section: Methodsmentioning
confidence: 99%